An elementary introduction to queueing systems - Chan, Wah Chun (World Scientific Publishing Company, 2014)
The book aims to highlight the fundamental concepts of queueing systems. It starts with the mathematical modeling of the arrival process (input) of customers to the system. It is shown that the arrival process can be described mathematically either by the number of arrival customers in a fixed time interval, or by the interarrival time between two consecutive arrivals. In the analysis of queueing systems, the book emphasizes the importance of exponential service time of customers. With this assumption of exponential service time, the analysis can be simplified by using the birth and death proc